The Compensation Space : An Approach Towards the Compensation Conundrum - Kuknor, Sunaina (Prabandhan: Indian Journal of Management, 2016)
It is said that compensation is not about how much is paid to an employee, but how much they are valued – with the tangibles (money, perks) only being a surrogate for the intangible. This lifts the whole understanding from mundane money to valued humans. For organizations, it is important to design what the compensation package says in terms of valuing the employee, before arriving at the tangible components of the compensation package. Naturally, the organization also spells out what the return value is for the compensation, which can cover performance, retention, innovation, and so on. Mass customized/ individualized compensation can be aspirational for an organization. This paper conceptualized a matrix which may help organizations on the path to dealing with the compensation conundrum. Using five catchy labels – need, greed, seed, deed, and freed – it provides a framework to design compensation in line with the strategic intent of the organization. It suggests how the components of the package can be designed in line with the strategic intent, and pinpoints what value is being emphasized in the design of the package. It also suggests that customized compensation can be worked out. Being conceptual, it is naturally open to debate and empirical validation.